Silicone/epoxy hybrid resins with tunable mechanical and interfacial properties for additive manufacture of soft robots. (March 2021) - Joseph, Vincent Sebastian; Calais, Theo; Stalin, Thileepan; Jain, Snehal; Thanigaivel, Naresh Kumar; Sanandiya, Naresh D.; Valdivia y Alvarado, Pablo
Highlights: A novel family of epoxy/silicone hybrid resins with tunable mechanical properties is reported for the additive manufacturing of advanced functional composite structures. The excellent chemical compatibility between the selected epoxy resins and silicone rubbers allows the tuning of the elastic modulus over unprecedent five orders of magnitude, from 20 kPa to 1.6 GPa, and the ultimate tensile strength and elongation at break from 0.3 to 35 MPa and from 1300% to 2.7%, respectively. With excellent interfacial toughness between close compositions, functionnally-graded materials of hybrid resins were designed to connect softest and hardest compositions and could sustained up to 1000 J m −2 . By controlling the rheological properties of pre-cured inks with nanoclay, hybrid resins could be processed by direct-ink-writing, enabling advanced fabrication of functional structures applicable to wearables, healthcare, and soft robotics. Abstract: The multi-material structures found in soft robot bodies, from stretchable elastomers to hard connectors, can display highly distinct physicochemical properties, challenging the engineering of robust interfaces required for long-term performance in real-world scenarios. Here, a novel family of hybrid resins combining platinum-catalyzed silicones with epoxy resins cured by acid anhydrides is reported to enable fabrication of functional multi-material bodies with strong interfaces. By adjusting the composition of the hybrid resins, the elastic modulus can be tuned over an unprecedent ratio of five orders of magnitude (from ~20 kPa to ~2 GPa) with outstanding interfacial toughness (from 1 to 3 kJ m −2 ). The excellent control of ink rheological behavior via nanoclay addition allows additive manufacturing by direct-ink-writing, enabling seamless control of topology and mechanical properties with sub-millimeter resolution in three dimensions. The significance of this new class of hybrid resins is demonstrated via the fabrication of various functional devices relevant to wearables, healthcare, and soft robotics. Overall, these hybrid resins open new frontiers for the fabrication of the next generation of robust soft robots using single continuous additive manufacturing processes. Graphical abstract: Image, graphical abstract